The Effectiveness of Group Counseling Services Using Self-Management Techniques on Students’ Learning Time Management - Elvidayani, Elvidayani; Wastuti, Sri Ngayomi Yudha (IAIN Kudus, 2026)
The Effectiveness of Group Counseling Services Using Self-Management Techniques on Students’ Learning Time Management. This study aims to determine the effectiveness of group guidance services with self-management techniques on student study time management at Sanggar Bimbingan Kepong Malaysia. The population of this study was 6 sixth-grade students, and the sample was taken purposively. The study used a quantitative approach with a quasi-experimental one-group pretest-posttest design. The pre-test results showed that out of 6 students, 3 students were in the low category and 3 students were in the medium category, while the post-test results showed that all students were in the very high category. The treatment was given in one meeting. Hypothesis testing using the Wilcoxon Signed Rank Test with the help of SPSS produced an Asymp. Sig = 0.028 <0.05, so H0 was rejected and H1 was accepted, indicating a significant change in student study time management after the treatment. This study contributes to the development of guidance and counseling (BK) science by strengthening evidence that self-management techniques in group guidance can improve students' time management skills, which is one of the important competencies in students' character and academic development. The results of this study provide implications for BK teachers, namely that the use of group guidance services with self-management techniques can be an effective strategy in fostering and improving students' study time management at school.Keywords: Group Guidance, Self Management, Study Time Management, Guidance and Counseling.